2022
DOI: 10.3390/cancers14133273
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α Inhibition Improves Anti-Tumor Immunity and Promotes the Efficacy of Stereotactic Ablative Radiotherapy (SABR)

Abstract: High-dose hypofractionated radiation such as SABR (stereotactic ablative radiotherapy) evokes an anti-tumor immune response by promoting a series of immune-stimulating processes, including the release of tumor-specific antigens from damaged tumor cells and the final effector phase of immune-mediated lysis of target tumor cells. High-dose hypofractionated radiation also causes vascular damage in tumors, thereby increasing tumor hypoxia and upregulation of hypoxia-inducible factors HIF-1α and HIF-2α, the master … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 100 publications
(238 reference statements)
0
9
0
Order By: Relevance
“…While a number of studies found that CFRT generates an increased level of both Treg and MDSC cells, expanding and promoting T cell dysfunction towards immunosuppression, it seems that HF schemes are more advantageous in stimulating the immune system [ 29 ]. Considering the effect on TME, in murine models, the comparison of CFRT with HFRT revealed that the latter fractionation schedule may inhibit hypoxia and reduce the recruitment of immunosuppressive cells into primary tumors, generating a microenvironment with lower PD-L1 levels and boosting not only local, but also systemic CD8- mediated anticancer immunity [ 30 ]; although, a large number of studies showed that high-dose/fraction irradiation may alter tumor blood vessels, increasing tumor hypoxia with the recruitment of immunosuppressive cells into tumors and a PDL-1 increase [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…While a number of studies found that CFRT generates an increased level of both Treg and MDSC cells, expanding and promoting T cell dysfunction towards immunosuppression, it seems that HF schemes are more advantageous in stimulating the immune system [ 29 ]. Considering the effect on TME, in murine models, the comparison of CFRT with HFRT revealed that the latter fractionation schedule may inhibit hypoxia and reduce the recruitment of immunosuppressive cells into primary tumors, generating a microenvironment with lower PD-L1 levels and boosting not only local, but also systemic CD8- mediated anticancer immunity [ 30 ]; although, a large number of studies showed that high-dose/fraction irradiation may alter tumor blood vessels, increasing tumor hypoxia with the recruitment of immunosuppressive cells into tumors and a PDL-1 increase [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A bulk of studies have validated that metformin also promotes the cancer-killing functions of CD8 + T cells in metabolic regulation-dependent manners ( Pearce et al, 2009 ; Chen et al, 2021b ; Chao et al, 2022 ). Metformin treatment downregulates immune checkpoint expression and glycolytic cancer flux in a HIF-1α inhibition-dependent manner, thereby improving ICB therapy ( Chung et al, 2021 ; Song et al, 2022b ). Furthermore, the metabolic rewiring effects-mediated by metformin can affect the metabolic interaction between cancer cells and non-malignant cells within TME.…”
Section: Available Glycolysis-targeted Therapiesmentioning
confidence: 99%
“…Understanding tumor immunology has revealed mechanisms and factors involved in the escape of cancer cells from immune surveillance and showed how cancer cells harness immune responses in favor of their proliferation. Exploring the role of factors such as immune checkpoints and immunosuppressive cytokines, as well as the downregulation of immune stimulatory biomolecules, along with the emergence of chronic inflammation that results in immune dysfunction and interferences with the intrinsic activity of the host immune cells, provides opportunities to help the immune system to attack malignant cells [ 162 , 163 ]. Nanocarriers, especially liposomes, have been exploited in immunotherapy, either as carriers or adjuvants in cancer vaccines [ 164 ], or for selective delivery of immunomodultory agents [ 165 , 166 , 167 ].…”
Section: Liposome-based Cancer Immunotherapymentioning
confidence: 99%